EVALUATION OF CORPORATE DIGITAL ANNUAL REPORTING - Singh Walia, Harpreet (International Journal of Research -GRANTHAALAYAH, 2016)
Corporate reporting process has undergone a complete makeover in the recent times. It has affected companies and stakeholders in the most positive way as ever. Emergence of digital annual reporting is also one of the paramount changes that is slowly taking the place of old traditional printed annual reports. Nowadays many companies are using digital annual reporting as an effective medium to distribute its annual reports to the stakeholders. Digital annual reporting use the electronic coupled with internet medium for fast and cost-effective corporate reporting. The benefits are much more than the cost of this new generation method. Hence now many companies understand the significance of digital annual reporting and are trying to embed the medium as an essential part of their reporting practices. But this medium is also not free from defects and shortcomings. In this article a brief evaluation of digital annual reporting is being done to find out the various benefits and limitations of using digital annual reporting by the corporate companies.